INTENTIONS TOWARDS SOCIAL ENTREPRENEURSHIP AMONG UNIVERSITY STUDENTS IN INDIA - Chengalvala, Sarada; Rentala, Satyanarayana (International Journal of Research -GRANTHAALAYAH, 2017)
Social entrepreneurship is the ability to be an agent of change for various economic, environmental, social and political issues at local and global levels. It is believed that exposure of youth to social entrepreneurial theories and practice in institutes of higher education can impact this change. The students in various universities armed with knowledge and skills that they gained, with the support of entrepreneurial culture and environment while in campus may help them to choose social entrepreneurship as a career option after their formal education. In this backdrop, this research aims to identify the levels of entrepreneurial intentions and social entrepreneurship among University students. A sample of 150 university students across the country was included in the research. Factor analysis was used to identify factors that influence social entrepreneurship intentions. Five factors which influence social entrepreneurship intentions were identified - social entrepreneurship interest, entrepreneurial attitude, proactive personality, entrepreneurship education and perceived behavioral control. Furthermore, correlation analysis was conducted to investigate the relationship amongst social entrepreneurship intentions factors. The results were significant which indicated that there was a positive linear inter-factor association.